Analisis Brand Awareness dan Brand Image Terhadap Keputusan Pembelian Produk Street Boba (Studi Kasus di DKI Jakarta) - Maulina Agustin; Anjar Dwi Astono (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This research was conducted to find out how much the independent variable effect on the dependent variable. Researchers chose Street Boba as the object of research which was then carried out in March-May. The population in this study are Street Boba consumers who are domiciled in DKI Jakarta. The sample in this study was 110 respondents. Data collection techniques that used in this study using a questionnaire method. Before the questionnaire was distributed, first tested by taking a sample of 30 respondents. Quantitative analysis includes validity and reliability tests, multiple regression analysis, hypothesis testing through t test and f test and analysis of the coefficient of determination (R2). The results of the study concluded that Hypothesis testing using the t test shows that the two independent variables studied was proven to have a significant partial effect on the dependent variable. By Simultaneous Brand Awareness and Brand Image variables have a significant effect on buying decision.